2019
DOI: 10.1002/pc.25307
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the hybrid materials based on carbon nanotubes and tannic acid on the rheological, thermal and mechanical performances of nitrile butadiene rubber composites

Abstract: In this work, hybrid composites are consisting of single wall carbon nanotubes (CNT) and tannic acid (TA) embedded in nitrile butadiene rubber (NBR) matrix using kneading followed by the hot‐pressing method. The CNT and TA were mixed to NBR at different ratio and the obtained composites were subjected to morphological, rheological and thermal analysis as well as mechanical properties. The tensile test results manifested that both CNT and TA can be used as the reinforcing fillers, while the NBR composites fille… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 46 publications
(50 reference statements)
2
6
0
Order By: Relevance
“…The toughness and strength were enhanced by up to 190% and 200%, respectively (comparable to commercial fillers at much higher loadings). The results discussed in the previous paragraph (see [ 122 ]) are in quite good agreement with this, although the formed interpenetrating network seems to be even more favorable than uncontrolled blending. A different, quite outstanding approach towards such a material utilizes enzyme-mimetic catalytic crosslinking of condensed tannin which can yield flexible hydrogel networks of various properties.…”
Section: Hybrid Materialssupporting
confidence: 78%
See 1 more Smart Citation
“…The toughness and strength were enhanced by up to 190% and 200%, respectively (comparable to commercial fillers at much higher loadings). The results discussed in the previous paragraph (see [ 122 ]) are in quite good agreement with this, although the formed interpenetrating network seems to be even more favorable than uncontrolled blending. A different, quite outstanding approach towards such a material utilizes enzyme-mimetic catalytic crosslinking of condensed tannin which can yield flexible hydrogel networks of various properties.…”
Section: Hybrid Materialssupporting
confidence: 78%
“…On the other hand, the authors suggested the ability of the epoxy matrix to achieve strong interfacial interaction with the carbon nanotubes via the tannin–polyethylenimine functionalization as a second factor enabling the enhancement. A similar positive effect was observed when tannic acid was added to nitrile butadiene rubber along with carbon nanotubes [ 122 ]. For instance, after the vulcanization of the rubber with carbon nanotubes but without tannic acid, the toughness was enhanced by roughly 40% while the presence of tannic acid could substantially elevate this effect to an enhancement of roughly 160%.…”
Section: Hybrid Materialssupporting
confidence: 57%
“…The two characteristic peaks also prove the presence of Ag NPs at 2θ of 36.1°and 41.3°, marked by their indices ((111) and ( 200)). The peak at approximately 2θ = 25°was observed in TA, attributed to TA's characteristic peaks [34,35]. The TiO 2 is indexed as hexagonal anatase form (ICDS: 98-015-4601) [36].…”
Section: Characterizationmentioning
confidence: 99%
“…The wonderful levels of mechanical, electrical, thermal, and physical properties of carbon nanotubes (CNT) have motivated the increasing interests for the investigation of composites containing CNT as polymer/CNT nanocomposites (PCNT) . The electrical conductivity of CNT reaches to 10 6 S/m, but the polymer matrices usually show the conductivity of 10 −16 to 10 −12 S/m .…”
Section: Introductionmentioning
confidence: 99%